Das zusammengedrängte Gedenken Leopold Kupelwiesers Freskenzyklus in der niederösterreichischen Statthalterei - Eyb-Green, Sigrid (Verlag Bibliothek der Provinz GmbH, 2016)
In 1847, the Austrian painter Leopold Kupelwieser (1796-1862) was commissioned to execute a fresco cycle in the Ceremonial Hall of the Niederösterreichische Statthalterei (Lower Austrian Government Building, Vienna), depicting scenes from Austrian history. Iconographic aspects of each painting, using pictorial and literary sources as well as pointing out biographical connections and artistic forebears and influences, are being discussed. The complex interplay between art technology and conceptual statements manifests itself particularly articulate in the focal point of cartoon and fresco; accordingly, this study approaches Kupelwiesers work through the description of the materials he used and the way he processed them.